ANALISIS PERBEDAAN PENDAPATAN PETANI JAGUNG SEBELUM DAN SESUDAH BERDIRINYA PERUSAHAAN PT. SEGER AGRO NUSANTARA DI DESA TEKASIRE KABUPATEN DOMPU NUSA TENGGARA BARAT - Syarif Mahdi; Sudarti Sudarti; Zainal Arifin (Jurnal Ilmu Ekonomi JIE, 2019)
This study takes the title "Analysis of Differences in Corn Farmer Income Before and After the Establishment of the Company PT. Seger Agro Nusantara in Tekasire Village, Dompu Regency, West Nusa Tenggara ". The purpose of this study was to determine the characteristics of corn farmers, and differences in income of corn farmers before and after the existence of PT. Seger Agro Nusantara in Tekasire Village, Dompu Regency, West Nusa Tenggara. This research was conducted in Manggelewa Sub-District more precisely in Tekasire Village, Dompu Regency, West Nusa Tenggara. the type of research used is quantitative descriptive which is analyzed using a different test (t test) with the SPSS application. From the results of the study it can be concluded that the income of corn farmers before and after the establishment of the company looks very different after being tested, because at the time before the establishment of the company in 2015 the selling price of corn was Rp.1000 / kg whereas after the establishment the company had quite high purchasing power amounting to Rp.3,200 / Kg, so the highest income of one corn farmer before the company was Rp.23,366,000 / harvest period (4 months), while after the establishment of the company the farmer's income increased by Rp.89,284,000 / harvest period (4 month). It will automatically increase the income efficiency of corn farmers who previously only 6.88 and have increased to 16.72, as well as other corn farmers who have increased income after the establishment of the company PT. Seger Agro Nusantara.Keywords: Companies, Farmers, Income